Are There Any Differences in the Neural and Extracellular Matrix Proteins Density Between Children and Adults with Intrinsic Ureteropelvic Junction Obstruction? - KAYA, CEVDET; ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; ERCAN, FERİHA; TANIDIR, YILÖREN (GALENOS YAYINCILIK, 2017)
Objective: To compare changes in connective, neural and muscle tissues, and extracellular matrix in child and adult patients so that we can create a more objective view on the timing of surgery. Materials and Methods: Twenty-six patients, who were operated for ureteropelvic junction (UPJ) obstruction in our clinic between September 2014 and May 2016, were included in the study. For the evaluation of connective tissue, Masson's trichrome staining was used. Muscle, extracellular matrix elements and neural tissue were evaluated with immunohistochemistry using alpha-smooth muscle actin (a-SMA), Tenascin C and S100, respectively. Microscopically, the tissues were scored according to their staining density (0: No staining; 1: Minor; 2: Moderate, 3: Dense). Results: There were 12 children and 14 adults in the study groups. The initial evaluation showed no statistically significant difference between studied tissue types with respect to staining density for all parameters (Masson: p=0.414, a-SMA: p=0.204, Tenascin-C: p=0.264, S100: p=0.534). There was no statistically significant correlation between staining density and renal function percentage of the affected kidney (Masson: r=0.454, p=0.051, alpha-SMA: r=-0.323, p=0.177 -Tenascin-C: r=0.290, p=0.229 -S100: r=-0.080, p=0.744). Conclusion: Our preliminary study showed some structural changes between adult and child patients but there is no statistically significant difference between the groups with respect to staining density scores. These results state that although UPJ obstruction is an ongoing process, there is no correlation between the histological deterioration degree of the UPJ segment and the loss on renal function for both children and adults.
Keywords: Extracellular matrix; immunohistochemistry; muscle tissue; connective tissue; neural tissue; ureteropelvic junction; RENAL-FUNCTION; PYELOPLASTY; HYDRONEPHROSIS; TENASCINS; IMPROVE